1993
DOI: 10.1111/j.1365-2869.1993.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ipsapirone, a 5‐HT1A agonist, on sleep/wakefulness cycles: probable post‐synaptic action

Abstract: The effects of ipsapirone, a ligand of the 5-HT1A receptors and a new potential anxiolytic, on sleep/wakefulness regulation were examined in the rat. Injected i.p. at 1, 3 and 5 mg kg-1, this compound induced a dose-dependent reduction of paradoxical sleep for 2 to 4 hours, followed, at a dose of 5 mg kg-1, by a secondary rebound. The other states of vigilance were not modified, except at the latter dose where the amounts of wakefulness were enhanced initially and decreased secondarily, while those of SWS were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 28 publications
4
27
0
1
Order By: Relevance
“…This is in agreement with results obtained in depressed patients vs controls (Gillin et al, 1996;Seifritz et al, 1998), but it contrasts with the augmented hypothermia response to the same agonist found in H mice (El Yacoubi et al, 2003). This apparent discrepancy is due to the fact that the sleep response is mediated by post-synaptic 5-HT 1A receptors (Tissier et al, 1993), possibly at pontine level (Horner et al, 1997), whereas the hypothermic response is mediated by pre-synaptic (auto-) receptors (Goodwin et al, 1985). Indeed, the latter receptors are functionally hypersensitive in H mice (El Yacoubi et al, 2003), whereas the post-synaptic ones are unchanged, as observed under various experimental conditions (Fabre et al, 2000, Hensler, 2003.…”
Section: Muscarinic-and 5-ht 1a -Receptor-mediated Regulations Of Remsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in agreement with results obtained in depressed patients vs controls (Gillin et al, 1996;Seifritz et al, 1998), but it contrasts with the augmented hypothermia response to the same agonist found in H mice (El Yacoubi et al, 2003). This apparent discrepancy is due to the fact that the sleep response is mediated by post-synaptic 5-HT 1A receptors (Tissier et al, 1993), possibly at pontine level (Horner et al, 1997), whereas the hypothermic response is mediated by pre-synaptic (auto-) receptors (Goodwin et al, 1985). Indeed, the latter receptors are functionally hypersensitive in H mice (El Yacoubi et al, 2003), whereas the post-synaptic ones are unchanged, as observed under various experimental conditions (Fabre et al, 2000, Hensler, 2003.…”
Section: Muscarinic-and 5-ht 1a -Receptor-mediated Regulations Of Remsupporting
confidence: 90%
“…In contrast to muscarinic receptors, activation of 5-HT 1A receptors by 8-OH-DPAT induced a dose-dependent reduction of REM sleep amounts and an increase in REM sleep latency in both mouse lines, as observed in other mouse strains (Boutrel et al, 1999), in rats (Tissier et al, 1993), and also in humans (Driver et al, 1995). This effect is most probably accounted for by an agonist action of 8-OH-DPAT at 5-HT 1A but not 5-HT 7 receptors (Wood et al, 2000).…”
Section: Muscarinic-and 5-ht 1a -Receptor-mediated Regulations Of Remsupporting
confidence: 58%
See 1 more Smart Citation
“…Among the receptors at which 5-HT in excess could act to induce PS inhibition, the 5-HT 1A and 5-HT 1B types appeared as the most relevant candidates (Dzoljic et al, 1992;Tissier et al, 1993;Bjorvatn and Ursin, 1994;Monti et al, 1995;Bjorvatn et al, 1997;Boutrel et al, 1999Boutrel et al, , 2002. Indeed, we can conclude from the present study that 5-HT 1A receptors are primarily involved in such a PS inhibition because the effect of citalopram on sleep was markedly reduced in 5-HT 1A À/À, but globally unchanged in 5-HT 1B À/À, mutants compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in several species and notably the rat (Pastel and Fernstrom, 1987;Ursin et al, 1989;Lelkes et al, 1994;Maudhuit et al, 1994;Neckelmann et al, 1996b), the hamster (Gao et al, 1992), and also in humans (Van Bemmel et al, 1993;Hendrickse et al, 1994), the most consistent action of SSRIs is a reduction of paradoxical sleep (PS), which is sometimes associated with an enhancement of wakefulness (W) and a secondary increase in slow wave sleep (SWS) (Maudhuit et al, 1994;Ursin, 2002). In the same manner, systemic treatment with selective agonists at 5-HT 1A and 5-HT 1B receptors induces an inhibition of PS and an enhancement of wakefulness, notably in rodents (Dzoljic et al, 1992;Tissier et al, 1993;Bjorvatn and Ursin, 1994;Monti et al, 1995;Bjorvatn et al, 1997;Boutrel et al, 1999Boutrel et al, , 2002. In contrast, inactivation of 5-HT 1A and 5-HT 1B receptors (notably in mice with genetic deletions targeted at these receptors) facilitates the expression of PS (Boutrel et al, 1999(Boutrel et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%